Robo-advisory for Islamic financial institutions: shari’ah and regulatory issues - Adam Sa'ad, Auwal; Syed Jaafar Alhabshi, Syed Musa; Hassan, Rusni; Mohd Noor, Azman (Turin University Italy, 2020)
Artificial intelligence (AI) is the next global game changer in all big data and other technology-based platforms including Islamic financial services. At the forefront of AI applications in financial services is Robo-Advisor. Its potential disruption of the Islamic financial services is imminent as it is being considered by some institutions due to its innovative virtual advisory and the absence of human factor intervention in the decision-making process. Currently the Islamic financial services industry is constantly guided by prescribed Shari’ah related fatwah or rulings for innovative financial products with reference to Shari’ah compliance. Robo-advisors may then be considered to ease the iterative juristic review process to facilitate timely and more robust Shari’ah legal opinions on those products. And since these Robo-Advisors are allegedly swift and smarter to support human judgment this might help achieve more timely, effective and efficient design and delivery of Islamic financial services. This paper aimed at investigating the potential Shari’ah and regulatory issues surrounding Robo-Advisors while adopting the relevant opinions and understanding of Shari’ah classical and contemporary scholars. It also seeks to examine the legal implications of Robo-Advisors in the Islamic financial industry and explore the technical requirements of this emerging phenomenon. The paper also looks into the current market volume of this new artificial intelligence mechanism and predicts the future of this disruptive technology in the Islamic finance industry.